3d $$ \mathcal{N} $$ = 4 OPE coefficients from Fermi gas - Chester,SM; Kalloor,RR; Sharon,A (Journal of High Energy Physics, 2020)
A bstract The partition function of a 3d $$ \mathcal{N} $$ N = 4 gauge theory with rank N can be computed using supersymmetric localization in terms of a matrix model, which often can be formulated as an ideal Fermi gas with a non-trivial one-particle Hamiltonian. We show how OPE coefficients of protected operators correspond in this formalism to averages of n -body operators in the Fermi gas, which can be computed to all orders in 1 /N using the WKB expansion. We use this formalism to compute OPE coefficients in the U( N ) k × U( N ) −k ABJM theory as well as the U( N ) theory with one adjoint and N f fundamental hypermultiplets, both of which have weakly coupled M-theory duals in the large N and finite k or N f regimes. For ABJM we reproduce known results, while for the N f &l